Harrod, Balassa, and Samuelson (re)visit Eastern Europe - Robert J. Sonora; Josip Tica (Cogent Economics & Finance, 2014)
In this paper, we investigate the Harrod-Balassa-Samuelson (HBS) hypothesis in 11 Central and Eastern European transition countries. Unlike previous research, we test the HBS hypothesis with NACE 6 quarterly data which enables us to divide data into tradable and nontradable sectors without requiring unrealistic assumptions on the nature of the data. Contrary to previous results, we are only able to find evidence for univariate HBS effects in Bulgaria, Croatia, Hungary, and Poland. However, using panel cointegration tests, we find strong statistical evidence for the HBS hypothesis within countries and across countries. Our results also demonstrate that cross-country HBS holds under the assumption that the law of one price for tradables does not hold. Finally, we find, contrary to theory, that government consumption negatively impacts relative prices. The policy implications are that failing to acknowledge the peculiarities of the transition process results in suboptimal monetary policy.
Keywords: E31; F31; F41; 330; Harrod-Balassa-Samuelson effect; price convergence; transition countries; panel cointegration tests